A randomised controlled trial of small particle inhaled steroids in refractory eosinophilic asthma (SPIRA) - Hodgson, David; Anderson, John; Reynolds, Catherine; Meakin, Garry; Bailey, Helen; Pavord, Ian; Shaw, Dominick E.; Harrison, Timothy W. (BMJ Publishing Group, 2015)
Background: Some patients with refractory asthma have evidence of uncontrolled eosinophilic inflammation in the distal airways. While traditional formulations of inhaled steroids settle predominantly in the large airways, newer formulations with an extra-fine particle size have a more peripheral pattern of deposition. Specifically treating distal airway inflammation may improve asthma control.